Dissecting the genetic control of root and leaf tissue-specific anthocyanin pigmentation in carrot (Daucus carota L.) - Bannoud, Florencia; Ellison, Shelby L.; Paolinelli, Marcos; Horejsi, Thomas; Senalik, Douglas A.; Fanzone, Martín Leandro; Iorizzo, Massimo; Simon, Philipp W.; Cavagnaro, Pablo (Springer, 2019)
Purple carrots can accumulate large quantities of anthocyanins in their root tissues, as well as in other plant parts. This work investigated the genetic control underlying tissue-specific anthocyanin pigmentation in the carrot root phloem and xylem, and in leaf petioles. Inheritance of anthocyanin pigmentation in these three tissues was first studied in segregating F2 and F4 populations, followed by QTL mapping of phloem and xylem anthocyanin pigments (independently) onto two genotyping by sequencing-based linkage maps, to reveal two regions in chromosome 3, namely P1 and P3, controlling pigmentation in these three tissues. Both P1 and P3 condition pigmentation in the phloem, with P3 also conditioning pigmentation in the xylem and petioles. By means of linkage mapping, phylogenetic analysis, and comparative transcriptome (RNA-Seq) analysis among carrot roots with differing purple pigmentation phenotypes, we identified candidate genes conditioning pigmentation in the phloem, the main tissue influencing total anthocyanin levels in the root. Among them, a MYB transcription factor, DcMYB7, and two cytochrome CYP450 genes with putative flavone synthase activity were identified as candidates regulating both the presence/absence of pigmentation and the concentration of anthocyanins in the root phloem. Concomitant expression patterns of DcMYB7 and eight anthocyanin structural genes were found, suggesting that DcMYB7 regulates transcription levels in the latter. Another MYB, DcMYB6, was upregulated in specific purple-rooted samples, suggesting a genotype-specific regulatory activity for this gene. These data contribute to the understanding of anthocyanin regulation in the carrot root at a tissue-specific level and maybe instrumental for improving carrot nutritional value.